Ichnotaxonomy, origin and paleoenvironment of Quaternary insect cells from Fuerteventura, Canary Islands, Spain - Genise, Jorge Fernando (2003)
On Fuerteventura, Canary Islands, micritic and silty to sandy insect cells are abundant, in well-exposed Quaternary terrestrial sediments and calcretes. Previous authors regarded these cells as hymenopteran in origin, referring them to the ichnogenus Celliforma. However, a new study of cell shape, cell wall thicknesses, cell lining, apertural closure, construction materials and cell aggregation and clustering, indicates that some of these fossils may be referable to the ichnogenus Palmiraichnus or an unnamed ichnogenus of the Celliformidae, attributed to bees. Other cells are referable to the ichnogenus Rebuffoichnus, considered to be coleopteran pupal cells. Similarities between this Quaternary assemblage and better-known Late Cretaceous to Early Tertiary insect cell assemblages from South America, support an earlier suggestion that the Fuerteventuran cell assemblages developed during periods of relatively increased rainfall in an overall semiarid paleoclimate.